Emily Dickinson du côté de Shakespeare - Chevrier-Bosseau, Adeline (Presses universitaires Blaise-Pascal, 2024)
Emily Dickinson’s poetry showcases a dramatic kind of lyricism: each poem becomes a scene where the lyric voice changes shape, tone, and even gender. Strongly influenced by Shakespeare’s work and by the extremely theatrical culture of Victorian America, Dickinson stages the lyrical self at its most theatrical. The fact that the Elizabethan playwright and poet’s idiosyncratic theater was the main reference for Dickinson’s conception of drama and theatricality invites us to broaden our conception of lyricism. Although some recurrences of a more traditional approach to lyricism as an outpouring of intimate feelings appear at times – mostly tainted with a great deal of irony – lyricism will mainly be considered as the energy fueling life into the poem. The theater is for Emily Dickinson the spring of this lyrical energy, the transformative force and the crucial structure at the heart of her poetic writing.